2022
DOI: 10.3390/v14071461
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Utilization of Disulfide-Bonded SARS-CoV-2 Receptor Binding Domain of Spike Protein Synthesized by Wheat Germ Cell-Free Production System

Abstract: The spike protein (SP) of SARS-CoV-2 is an important target for COVID-19 therapeutics and vaccines as it binds to the ACE2 receptor and enables viral infection. Rapid production and functional characterization of properly folded SP is of the utmost importance for studying the immunogenicity and receptor-binding activity of this protein considering the emergence of highly infectious viral variants. In this study, we attempted to express the receptor-binding region (RBD) of SARS-CoV-2 SP containing disulfide bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…We first tested a three-antigen MISPA assay that targeted two SARS-CoV-2 antigens of the original Wuhan strain, receptor-binding domain (wRBD) of the spike protein and nucleocapsid (NC), along with a negative control protein, the green fluorescent protein (GFP). The wRBD is a glycosylated protein with four disulfide bonds, and serum samples from COVID-19 patients showed only a weak response to IVTT-produced wRBD ( 13 ). Therefore, we expressed it in Expi293F cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first tested a three-antigen MISPA assay that targeted two SARS-CoV-2 antigens of the original Wuhan strain, receptor-binding domain (wRBD) of the spike protein and nucleocapsid (NC), along with a negative control protein, the green fluorescent protein (GFP). The wRBD is a glycosylated protein with four disulfide bonds, and serum samples from COVID-19 patients showed only a weak response to IVTT-produced wRBD ( 13 ). Therefore, we expressed it in Expi293F cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell-based production is more cumbersome but necessary for some proteins. The majority of proteins were produced in MISPA using an IVTT coupled expression system, which has been employed extensively in the production of tens of thousands of proteins for use in serological studies ( 13 19 ). This HeLa cell lysate-based IVTT, which includes both human ribosomes and chaperone proteins, can produce folded and enzymatically active proteins ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the RBD is a determinant of reduced S1/S2 proteolysis in the Omicron BA.1 spike [ 26 ], and the N-terminal domain of the Delta spike allosterically modulates S1/S2 processing [ 27 ]. Furthermore, similar to the C488 mutations in RBD, which disrupt the C480–C488 disulfide bond of the spike protein, Yamaoka et al recently showed that disulfide-bond formation is critical for RBD functioning, and C488A and C379A mutations lost their ACE2-binding ability [ 28 ]. In addition, Zhang et al showed that the C301F and C379F mutations eliminate the C291–C301 and C379–C432 disulfide bonds located in the S1 N-terminal domain and RBD, respectively, thus causing the S1/S2 processing loss of the spike protein [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the RBD is a determinant of reduced S1/S2 proteolysis in the omicron BA.1 spike [21], and the N-terminal domain of the delta spike allosterically modulates S1/S2 processing [22]. Furthermore, similar to the C488 mutations in RBD, which disrupts the C480-C488 disulfide bond of the spike protein, Yamaoka et al recently showed that disulfide bond formation is critical for RBD functioning, and C488A and C379A mutations lost their ACE2-binding ability [23]. In addition, Zhang et al showed that the C301F and C379F mutations eliminate the C291-C301 and C379-C432 disulfide bonds located in the S1 N-terminal domain and RBD, respectively, thus causing S1/S2 processing loss of the spike protein [14].…”
Section: Discussionmentioning
confidence: 99%